2016
DOI: 10.1016/j.aogh.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Children's Environmental Health in Brazil

Abstract: In the region of the Americas, approximately 100,000 children under the age of 5 years die each year due to environmental hazards. Brazil, due to its large size and wide range of environmental challenges, presents numerous hazards to children's health. The aim of this study was to systematically review the scientific literature that describes children's exposures to environmental pollutants in Brazil and their effects on Brazilian children's health. A systematic review of the scientific literature was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 104 publications
2
12
0
1
Order By: Relevance
“…Our findings corroborate previous studies with African children (Congo, South Africa, and Uganda) that showed significant associations between LBW and low values of growth indicators (Mackay et al, ; Namiiro et al, ; Njokanma et al, ). In addition, our findings are aligned with studies from low and middle‐income countries regarding the association between LBW and later body composition (Froes Asmus, Camara, Landrigan, Claudio, ; Muhardi et al, ). High levels of stunting are associated with poor socioeconomic conditions, increased risk of illness, and/or inappropriate feeding practices (World Health Organization, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings corroborate previous studies with African children (Congo, South Africa, and Uganda) that showed significant associations between LBW and low values of growth indicators (Mackay et al, ; Namiiro et al, ; Njokanma et al, ). In addition, our findings are aligned with studies from low and middle‐income countries regarding the association between LBW and later body composition (Froes Asmus, Camara, Landrigan, Claudio, ; Muhardi et al, ). High levels of stunting are associated with poor socioeconomic conditions, increased risk of illness, and/or inappropriate feeding practices (World Health Organization, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…It is estimated that 99% of the poisoning cases of pesticide exposure occur in low and middle-income countries [30], but contrastingly most studies included in this review were located in high-income countries. Although some children's health effects of pesticide exposure have been studied recently in lower income countries [31][32][33], respiratory outcomes are still understudied.…”
Section: Resultsmentioning
confidence: 99%
“…In Latin America, the influence of environmental factors on children’s health is related to known risks, such as water contamination, emerging factors related to climate change and exposure to toxic contaminants [ 26 ]. Children under five years of age who live in unfavorable socioeconomic conditions in low- and middle-income countries have greater exposure to poverty, malnutrition, poor housing conditions, and poor basic sanitation, which directly influence their healthy development [ 27 ].…”
Section: Resultsmentioning
confidence: 99%